The identity of a public servant (the case of local government) - Mbatani, Mabotlhale (My University, 2021)
Bureaucratic administration literature has previously considered a variety of explanations for public servants’ decision-making behaviours, including various inherent and extrinsic motivations that range from lack of skills to the venal and corrupt behaviours of public servants. The study examines the motives for the actions of public servants in the City of Johannesburg metropolitan municipality. Some of these actions may carry sanctions, according to prescribed rules of the municipality and government in general; or they may deviate from the norms of public administration. Using the logics of appropriateness framework, the research argues that public servants who act in these rule-breaking and deviant ways, may do so in the interests of the municipality and not because they have personal or corrupt reasons for doing so. Rather, public servants pursue deviant courses of action, which become patterns as they are repeated, precisely because they are working within several constraints that are not considered by prescribed laws and regulations. Thus, public servants will use only the rules that they deem appropriate when faced with constraints and in situational environments.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Organisational and institutional Studies to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021